Computer Network Audit using Wireshark and Metasploit Framework (Case Study: STMIK STIKOM Bali Jimbaran Campus II) - Rahardian, Rifky Lana; Anshari, Muhammad; Sastra, Nyoman Putra (International Journal of Engineering and Emerging Technology, 2017)
Advances in Information and Communication Technology (ICT) has been widely used by various organizations including educational institutions. One of the educational institutions that always take advantage of ICT in business processes as well as lectures there STIKOM Bali Jimbaran Campus II. STIKOM Bali Jimbaran Campus II is a private college branch of STMIK STIKOM Bali located at Jl. Raya Kampus Udayana Bali Jimbaran. The campus is still relatively new, a new due process entered its second year in the lecture. In terms of information systems and business processes that run STIKOM Bali Jimbaran Campus II refers to the Campus Master in Renon. Network architecture on STMIK STIKOM Bali Campus II Jimbaran arguably not perfect, for the authors will try to conduct an audit of computer networks using Wireshark and Metasploit on STMIK STIKOM Bali Campus II Jimbaran order to produce an output in the form of advice in the development of network architecture at STMIK STIKOM Bali Campus II Jimbaran future.